Comunidade Visível: narradores de imagens e memórias do Poço da Draga - Kardozo, Felipe Camilo Mesquita (2021)
This text seeks to understand how the sharing of personal collections of images enhances the production of constellations of memories, promotes self-narratives and feelings of belonging. Departing from Poço da Draga neighborhood in Fortaleza, an exemplary case of resistance to recurrent attempts at removal, this thesis maps some of its persistent “image practices” carried out by its residents through old family albums, documentaries, guided tours and content sharing via mobile devices. We call “visible community”, on the one hand, only what its narrators and their ways of practicing photographs let us see, but it is also, on the other hand, all this multiplicity that makes us see and makes itself seen. Taking anthropological work as a philosophy with people inside (Ingold, 1992), we developed photography and video workshops in Poço with its residents and “corner memorialists”. We identified, through a shared ethnographic exercise, the commitment of these narrators in their “memory works” (Bosi, 1994), as a confrontation with the incessant threats of removal from their community and the fraying of the threads that weave their stories. The thesis also shows these narrators’ “image practices” in opposition to the necropolitics (Mbembe, 2018) operated against Black diasporic populations in Brazil and those considered undesirable.